The Contribution of Stool Culture to the Epidemiological Surveillance of Pathogenic Enterobacteria Isolated from 2011 to 2016 at the Medical Biology Laboratory of the National Hospital Amirou Boubacar Diallo in Niamey, Niger - Mamane Daouda Aminata; Oubayyou - Yaroukoy AMB; Mamadou Saidou (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2025)
Stool culture is a test generally requested during gastroenteritis, which is a very common pathology in developing countries. The aim of this study was to determine the prevalence of bacterial infectious gastroenteritis, particularly for Salmonella, Shigella, and E. coli infections, as well as the most effective antibiotics against these enteropathogenic germs. This was a retrospective descriptive study that took place from January 1st, 2011, to December 31st, 2016, at the Biology Laboratory of the National Hospital Amirou Boubacar Diallo (HNABD) in Niamey (Niger). Stool culture was performed according to the conventional bacteriology technique. The results showed that out of 8,102 samples analyzed, 2,940 revealed the presence of one of the 3 targeted germs. The isolation frequency for each was: 40.12% for E. coli, 10.89% for Shigella, and 9.78% for Salmonella. In infants, E. coli was the most isolated germ at 40.12%. As for Salmonella infections, they were more significant in adults with a rate of 19.24%. The most active antibiotics against Salmonella infections were ciprofloxacin with 85.7%, ceftriaxone and amikacin with 83.3%, and azithromycin with 80%. For Shigella, the most active antibiotics were amikacin with 100%, azithromycin with 93.8%, and nalidixic acid with 94.1%. For E. coli, the most effective antibiotics were amikacin with 90.7%, nalidixic acid with 75.3%, and ceftriaxone with 73.3%. These results highlight the need for vigilance because resistant strains are circulating, even though this resistance does not currently concern the most commonly used standard antibiotics in our context.